2016
DOI: 10.2147/ppa.s97912
|View full text |Cite
|
Sign up to set email alerts
|

The patient’s perspective of the feasibility of a patient-specific instrument in physiotherapy goal setting: a qualitative study

Abstract: BackgroundPatient participation in goal setting is important to deliver client-centered care. In daily practice, however, patient involvement in goal setting is not optimal. Patient-specific instruments, such as the Patient Specific Complaints (PSC) instrument, can support the goal-setting process because patients can identify and rate their own problems. The aim of this study is to explore patients’ experiences with the feasibility of the PSC, in the physiotherapy goal setting.MethodWe performed a qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 48 publications
(78 reference statements)
2
23
0
Order By: Relevance
“…Although elements of shared decision making were incorporated in the ‘planning treatment’ step, the physiotherapists did not fully involve the patients in this step, as has also been found in other studies [ 6 , 15 , 32 , 34 ]. The physiotherapists reported that not all patients wanted to participate, and this variety as regards patients’ preferences and abilities for participation has also been reported previously [ 6 , 8 , 11 , 35 37 ]. On the other hand, we also saw that patients were not always invited to participate, but were nevertheless satisfied about their conversations with the physiotherapists.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Although elements of shared decision making were incorporated in the ‘planning treatment’ step, the physiotherapists did not fully involve the patients in this step, as has also been found in other studies [ 6 , 15 , 32 , 34 ]. The physiotherapists reported that not all patients wanted to participate, and this variety as regards patients’ preferences and abilities for participation has also been reported previously [ 6 , 8 , 11 , 35 37 ]. On the other hand, we also saw that patients were not always invited to participate, but were nevertheless satisfied about their conversations with the physiotherapists.…”
Section: Discussionsupporting
confidence: 72%
“…To ensure reliability of the findings, the observations and patient files were scored independently, as recommended by Moore et al [ 39 ]. The intended use of the PSG was assessed by the Theory of Planned Behaviour questionnaire [ 28 , 41 ], with the content of the items being designed on the basis of the previous qualitative analysis [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the PSFS could be a tool to increase the patients´ self-awareness. 49 The time spent on the collaborative development of goals and the completion of the PSFS ranged from seven to 75 mins with a mean time on 28 mins. The database of rehabilitation measures states that it takes 4 mins to fill out the PSFS, 16 but this is without the collaborative goal-setting process.…”
Section: Discussionmentioning
confidence: 99%